RANCANG BANGUN SISTEM INFORMASI EVALUASI PENYELENGGARAAN PELATIHAN BIDANG KESEHATAN BERBASIS WEB - Hidayat, Irfansyah Maulana; Utomo, Budi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Evaluation is carried out to determine the effectiveness of the training. Evaluations that are still carried out manually/conventionally by collecting data through filling in instruments, have constraints including; Speed of submission of evaluation results report; delay in submitting the issuance of a certificate because the results of the report are used as a requirement for filing; limited storage space for files/report archives; risk of damage, loss of data either caused by viruses, dysfunction of device operations or accidental factors in deleting files. For this reason, a system is needed that can help and facilitate the evaluation process starting from recording, storing and reporting. System development was carried out using qualitative research methods and input-process-output system development methods using the steps of the System Development Life Cycle (SDLC) method of the prototype model. The PIECES Framework is used to analyze system requirements to produce user satisfaction levels. The results of the research are the design of a system consisting of Context Diagrams, Entity Relationship Diagrams (ERD), Table Relational Diagrams (TRD), Standard Operational Procedure (SOP) Flow Diagrams and Data Flow Diagrams (DFD). Users of this system are Admin (program person in charge), Assessors, Organizers and Leaders. This information system is able to facilitate the process of implementing and reporting the results of evaluation implementation, ease of accessing and presenting reports, providing data storage space and better data management compared to conventional methods.